Impact of residual disease at interval debulking surgery on platinum resistance and patterns of recurrence for advanced-stage ovarian cancer. Issue 10 (24th October 2021) - Greer, Anna; Gockley, Allison; Manning-Geist, Beryl; Melamed, Alexander; Sisodia, Rachel Clark; Berkowitz, Ross; Horowitz, Neil; Del Carmen, Marcela; Growdon, Whitfield B; Worley Jr, Michael
Abstract : Objective: To evaluate the impact of size and distribution of residual disease after interval debulking surgery on the timing and patterns of recurrence for patients with advanced-stage epithelial ovarian cancer. Methods: Patient demographics and data on disease treatment/recurrence were collected from medical records of patients with stage IIIC/IV epithelial ovarian cancer who were managed with neoadjuvant chemotherapy/interval debulking surgery between January 2010 and December 2014. Among patients without complete surgical resection but with ≤1 cm of residual disease, the number of anatomic sites (<1 cm single anatomic location vs <1 cm multiple anatomic locations) was used to describe the size and distribution of residual disease.  Results: A total of 224 patients were included. Of these, 70.5% (n=158) had a complete surgical resection, 12.5% (n=28) had <1 cm single anatomic location, and 17.0% (n=38) had <1 cm multiple anatomic locations. Two-year progression-free survival for complete surgical resection, <1 cm single anatomic location, and <1 cm multiple anatomic locations was 22.2%, 17.9% and 7%, respectively (p=0.007). Size and distribution of residual disease after interval debulking surgery did not affect location of recurrence and most patients had recurrence at multiple sites (complete surgical resection: 64.7%, <1 cm single anatomic location: 55.6%, and <1 cm multiple anatomic locations: 71.4%). Controlling for additional factors that may influence platinum resistance and surgical complexity, the rate of platinum-resistant recurrence was similar for patients with complete surgical resection and <1 cm single anatomic location (OR=1.07, 95% CI 0.40 to 2.86; p=0.888), but women with <1 cm multiple anatomic locations had an increased risk of platinum resistance (OR=3.09, 95% CI 1.41 to 6.78 p=0.005). Conclusions: Despite current classification as 'optimal, ' <1 cm multiple anatomic location at the time of interval debulking surgery is associated with a shorter progression-free survival and increased risk of platinum resistance.